Biblioterapia jako autonomiczna nauka. Rozważania wstępne - Czernianin, Halina; Czernianin, Wiktor (eBooki.com.pl, 2014)
Bibliotherapy as a science. Preliminary deliberations MAIN ISSUES: I. The Paradox of metonymic name; II. Determinants of literary autonomy of bibliotherapy; II. 1 Subject of bibliotherapy studies; II. 2. The Method as a constitutive determinant of bibliotherapy; III. Determinants of medical autonomy of bibliotherapy; IV. Determinants of pedagogical autonomy of bibliotherapy; V. Determinants of psychological autonomy of bibliotherapy; VI. Determinants of Library Science autonomy of bibliotherapy; VII. Summary
Keywords: therapeutic tool; the determinants of the autonomy of bibliotherapy; main research method bibliotherapy; triangle ofbibliotherapeutic relationship; bibliotherapy object of study